Characterization and Organic Compounds in Peloids from Mongolia - Dolmaa, G; Tserenpil, Sh; Ugtakhbayar, O; Shevchenko, SG; Kliba, LV; Voronkov, MG (Proceedings of the Mongolian Academy of Sciences, 2011)
The peloids are the important natural remedy all over the world. The physicochemical properties and some organic matters of peloids from 12 lakes in Mongolia were examined. These peloids belong to the continental hydrosulfide sticky peloid except Gurvan nuur peloid. Peloid from Lake Gurvan nuur was classified as a sapropel with high ash content. The peloid organic matters were investigated using chemical analysis and several analytical techniques, such as IR, and 13C NMR spectroscopy, GC/MS, gas chromatography. The concentration of total organic carbon in all continental hydrosulfide sticky peloids is ranged from 0.4% to 3.1%, but 15.3% in the sapropel. It shows that the majority of the peloids in Mongolia are hydrosulfide sticky peloid with lower organic matters than the sapropel and peat. In this study, no significant difference of chemical composition was observed between dissoluble and insoluble organic matters from peloids. Some classes of biomolecules, including lipid and carbohydrate, were identified. Biogenic stimulator humic acid (HA) is the major part of the peloid organic matter. HA concentration varied between 11.2% and 55.9% of total organic matter of peloids. The macromolecule of the sapropel HA exhibited a lower aromatization degree and more functional groups than other HAs, as revealed by the 13C NMR data and C/H ratio. The genesis of peloid organic matter is discussed in this paper. Our results suggest that the presence of known bioactive organic compounds, such as humic acid, lipid, and carbohydrate, as well as hydrogen sulfide causes the balneological value of peloids in Mongolia. DOI: http://dx.doi.org/10.5564/pmas.v0i4.42 Proceedings of the Mongolian Academy of Sciences 2009 No 4 pp.3-21